2016
DOI: 10.1007/s00436-016-4988-3
|View full text |Cite
|
Sign up to set email alerts
|

Nosema spp. infections cause no energetic stress in tolerant honeybees

Abstract: Host-pathogen coevolution leads to reciprocal adaptations, allowing pathogens to increase host exploitation or hosts to minimise costs of infection. As pathogen resistance is often associated with considerable costs, tolerance may be an evolutionary alternative. Here, we examined the effect of two closely related and highly host dependent intracellular gut pathogens, Nosema apis and Nosema ceranae, on the energetic state in Nosema tolerant and sensitive honeybees facing the infection. We quantified the three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 56 publications
2
25
0
1
Order By: Relevance
“…Interestingly, Huang et al (2012) showed a higher survival and increased immune responses in those tolerant bees compared to sensitive bees from an unselected lineage, despite suffering similar infection intensities of N. ceranae. In subsequent experiments, infected worker bees from this Nosema tolerant linage appeared to neither experience decreased rates of apoptosis (one form of PCD) (Kurze et al, 2015) nor energetic stress (Kurze et al, 2016b). A similar pattern was also found when comparing the midgut proteomes between infected workers of both the Nosema tolerant and a Nosema sensitive lineage (Kurze et al, 2016a).…”
Section: Introductionsupporting
confidence: 51%
See 2 more Smart Citations
“…Interestingly, Huang et al (2012) showed a higher survival and increased immune responses in those tolerant bees compared to sensitive bees from an unselected lineage, despite suffering similar infection intensities of N. ceranae. In subsequent experiments, infected worker bees from this Nosema tolerant linage appeared to neither experience decreased rates of apoptosis (one form of PCD) (Kurze et al, 2015) nor energetic stress (Kurze et al, 2016b). A similar pattern was also found when comparing the midgut proteomes between infected workers of both the Nosema tolerant and a Nosema sensitive lineage (Kurze et al, 2016a).…”
Section: Introductionsupporting
confidence: 51%
“…A breeding program selecting against Nosema over 20 years resulted in a Nosema tolerant honey bee lineage (Hatjina et al, 2014). Although Nosema prevalence reduced from 60-80% down to about 10% in selected colonies (Hatjina et al, 2014), individual bees were still susceptible to both Nosema apis and N. ceranae in laboratory experiments (Kurze et al, 2016b). Interestingly, Huang et al (2012) showed a higher survival and increased immune responses in those tolerant bees compared to sensitive bees from an unselected lineage, despite suffering similar infection intensities of N. ceranae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies revealed differences in honeybee susceptibility to infection by N. ceranae . Such differences may result from resistance or tolerance mechanisms mediated by the genetic variability of honeybees (Fontbonne et al ., ; Kurze et al ., ,b) but could also be due to life‐history traits of bee colonies used in the different studies. Indeed, sampled bees used for experimental studies may have been impacted in their colony by multiple factors including resources, contaminants or pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The alterations of the carbohydrate metabolism reflect the nutritional and energetic stress experienced by N. ceranae infected honey bees (Mayack and Naug, 2010;Aliferis et al, 2012;Vidau et al, 2014). Interestingly, this has not been observed in Nosema tolerant honey bees (Kurze et al, 2016). Energetic stress has been described in infected foragers that were hungrier than uninfected bees (Mayack and Naug, 2009), consuming more sugar Martín-Hern andez et al, 2011;Vidau et al, 2011).…”
Section: Genetic Diversity Of N Ceranaementioning
confidence: 99%